Pengembangan perangkat komunikasi data antar nelayan untuk distribusi titik tangkapan ikan - Satria Gunawan Zain; Abdul Rahman Patta (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is to produce a prototype radio modem that can support data communication between fishing boats. This type of research is applied research with prototyping models. With the stages of library research, system design and prototypes, model simulation, building design, testing, and evaluation. This communication device can be used for communication between fishing boats with a distance of no more than 10 km. This data communication device has a stable data transmission speed at 1200 bits per second. This device can be used to send information related to fishing boat activities such as fishing boat positions, distribution of fishermen's fishing points and other important information such as sea accident evacuation and monitoring of regional border violations from Indonesian fishermen.